2021
DOI: 10.31989/ffhd.v11i6.793
|View full text |Cite
|
Sign up to set email alerts
|

Suppressive effect of a single dose of monoglucosyl rutin on postprandial blood glucose elevation: A randomized, placebo-controlled, double-blind crossover study

Abstract: Objective: This study aimed to investigate the suppressive effect of a single dose of water-soluble α- glycosylated rutin (monoglucosyl rutin; MR) on postprandial blood glucose elevation in healthy subjects with relatively high fasting blood glucose levels.Methods: This randomized, placebo-controlled, double-blind crossover study enrolled 34 healthy Japanese adult subjects with relatively high fasting blood glucose levels. The study period ran from November 13, 2019, to March 19, 2020. All subjects were random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…For instance, a placebo-controlled trial conducted on 50 individuals with T2DM showed that a 3-month administration of rutin (500 mg/day) significantly reduced fasting blood glucose, insulin, HbA1c, and insulin resistance levels [ 48 ]. Moreover, a recent study on 34 healthy adult participants who received rutin showed a decrease in postprandial glycaemia [ 49 ].…”
Section: Clinical Investigations Of Antidiabetic Properties Of Natura...mentioning
confidence: 99%
“…For instance, a placebo-controlled trial conducted on 50 individuals with T2DM showed that a 3-month administration of rutin (500 mg/day) significantly reduced fasting blood glucose, insulin, HbA1c, and insulin resistance levels [ 48 ]. Moreover, a recent study on 34 healthy adult participants who received rutin showed a decrease in postprandial glycaemia [ 49 ].…”
Section: Clinical Investigations Of Antidiabetic Properties Of Natura...mentioning
confidence: 99%
“…Subjects: Table 1 shows the inclusion and exclusion criteria (TRIAL-1 and TRIAL-2). The inclusion and exclusion criteria were slightly modified based on the reports of Hashizume et al [20] and Baba et al [21].…”
Section: Introductionmentioning
confidence: 99%